Transcriptional dynamics of bile salt export pump during pregnancy: Mechanisms and implications in intrahepatic cholestasis of pregnancy. Issue 6 (19th May 2014) - Song, Xiulong; Vasilenko, Alexander; Chen, Yuan; Valanejad, Leila; Verma, Ruchi; Yan, Bingfang; Deng, Ruitang
<x xml:space="preserve">Abstract</x> Bile salt export pump (BSEP) is responsible for biliary secretion of bile acids, a rate‐limiting step in the enterohepatic circulation of bile acids and transactivated by nuclear receptor farnesoid X receptor (FXR). Intrahepatic cholestasis of pregnancy (ICP) is the most prevalent disorder among diseases unique to pregnancy and primarily occurs in the third trimester of pregnancy, with a hallmark of elevated serum bile acids. Currently, the transcriptional regulation of BSEP during pregnancy and its underlying mechanisms and involvement in ICP are not fully understood. In this study the dynamics of BSEP transcription in vivo in the same group of pregnant mice before, during, and after gestation were established with an in vivo imaging system (IVIS). BSEP transcription was markedly repressed in the later stages of pregnancy and immediately recovered after parturition, resembling the clinical course of ICP in human. The transcriptional dynamics of BSEP was inversely correlated with serum 17β‐estradiol (E2) levels before, during, and after gestation. Further studies showed that E2 repressed BSEP expression in human primary hepatocytes, Huh 7 cells, and in vivo in mice. Such transrepression of BSEP by E2 in vitro and in vivo required estrogen receptor α (ERα). Mechanistic studies with chromatin immunoprecipitation (ChIP), protein coimmunoprecipitation (Co‐IP), and bimolecular fluorescence complementation (BiFC) assays demonstrated that ERα directly interacted with FXR in living cells and in vivo in mice. Conclusion: BSEP expression was repressed by E2 in the late stages of pregnancy through a nonclassical E2/ERα transrepressive pathway, directly interacting with FXR. E2‐mediated repression of BSEP expression represents an etiological contributing factor to ICP and therapies targeting the ERα/FXR interaction may be developed for prevention and treatment of ICP. (Hepatology 2014;60:1992–2006)